Research Progress in Vitamin A and Autism Spectrum Disorder - Zhonghui Liu; Jingyu Wang; Qu Xu; Qin Hong; Jiansheng Zhu; Xia Chi (Behavioural Neurology)
Autism spectrum disorder (ASD) is a highly heterogeneous neurodevelopmental disorder. Over the past few decades, many studies have investigated the effects of VA supplementation in ASD patients and the relationship between vitamin A (VA) levels and ASD. VA is an essential micronutrient that plays an important role in various systems and biological processes in the form of retinoic acid (RA). Recent studies have shown that serum VA concentration is negatively correlated with the severity of ASD. The lack of VA during pregnancy or early fetal development can affect brain development and lead to long-term or even permanent impairment in the learning process, memory formation, and cognitive function. In addition, VA deficiency has been reported to have a major impact on the gastrointestinal function of children with ASD, while VA supplementation has been shown to improve the symptoms of ASD to a certain extent. This paper provides a comprehensive review of the relationship between VA and ASD.